Isolation of TSCD11 Gene for Early Chloroplast Development under High Temperature in Rice - Guonan Fang; Shenglong Yang; Banpu Ruan; Chaolei Liu; Anpeng Zhang; Hongzhen Jiang; Shilin Ding; Biao Tian; Yu Zhang; Noushin Jahan; Li Zhu; Guangheng Zhang; et al. (Rice, 2020)
Abstract Background Chloroplasts are essential for photosynthesis and play key roles in plant development. High temperature affects structure of chloroplasts and metabolism in plants. The seryl-tRNA synthetase plays an important role in translation of proteins. Although seryl-tRNA synthetase has been widely studied in microbes and animals, few studies have reported about its role in chloroplast development under high temperature in rice. Results In this study, we isolated a novel temperature-sensitive chlorophyll-deficient 11 (tscd11) mutant by ethyl methane sulfonate (EMS) mutagenesis of japonica variety Wuyujing7. The tscd11 mutant developed albino leaves at the 3-leaf stage under high temperature (35 °C), but had normal green leaves under low temperature (25 °C). Consistent with the albino phenotype, impaired chloroplasts, decreased chlorophyll content and increased ROS accumulation were found in the tscd11 mutant at 35 °C. Fine mapping and DNA sequencing of tscd11 revealed a missense mutation (G to A) in the eighth exon of LOC_Os11g39670 resulted in amino acid change (Glu374 to Lys374). The TSCD11 gene encodes a seryl-tRNA synthetase localized to chloroplast. Complementation test confirmed that the point mutation in TSCD11 is responsible for the phenotype of tscd11. TSCD11 is highly expressed in leaves. Compared with the wild type (WT), mutation in TSCD11 led to significant alteration in expression levels of genes associated with chlorophyll biosynthesis, photosynthesis and chloroplast development under high temperature. Conclusions TSCD11, encoding a seryl-tRNA synthetase localized to chloroplast, is vital to early chloroplast development at high temperature in rice, which help to further study on the molecular mechanism of chloroplast development under high temperature.